Carbohydrate versus fat ingestion during exercise - Jeukendrup, A. E. (Proceedings from the Gatorade International Triathlon Science II Conference, Noosa, Australia, November 7-8, 1999: Maximising Olympic Distance Triathlon Performance: A multi-disciplinary perspective, 1999)
Überblick zur Aufnahme von Fetten vs. Kohlenhydraten bei Belastung.